2018
DOI: 10.1038/s41467-018-06539-w
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies two risk loci for tuberculosis in Han Chinese

Abstract: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (Mtb), and remains a leading public health problem. Previous studies have identified host genetic factors that contribute to Mtb infection outcomes. However, much of the heritability in TB remains unaccounted for and additional susceptibility loci most likely exist. We perform a multistage genome-wide association study on 2949 pulmonary TB patients and 5090 healthy controls (833 cases and 1220 controls were genome-wide genotyped) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 55 publications
2
69
1
Order By: Relevance
“…It is more likely to be >10, as shown by the data for the infected control simulation, corresponding to a lifetime risk of TB between 40 and 80%. This OR is higher than those reported for the few SNPs identified by genome-wide association studies (GWAS) in TB (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). These 12 GWAS did not detect the effect of P1104A, as they did not report testing a recessive model.…”
Section: Discussioncontrasting
confidence: 56%
“…It is more likely to be >10, as shown by the data for the infected control simulation, corresponding to a lifetime risk of TB between 40 and 80%. This OR is higher than those reported for the few SNPs identified by genome-wide association studies (GWAS) in TB (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). These 12 GWAS did not detect the effect of P1104A, as they did not report testing a recessive model.…”
Section: Discussioncontrasting
confidence: 56%
“…These results indicate that ERAP2 may play a significant role in TB resistance. However, in a previous GWAS study in China, no association was identified between TB and ERAP genes (Chen et al, 2016a;Zheng et al, 2018). The race, sample size, characteristics of the patients and controls, and the genotyping methods used, are some of the factors that may affect the association study results.…”
Section: Discussionmentioning
confidence: 96%
“…The genes involved in antigen presentation, induction and function of cytokines/chemokines, and associated receptors have been suggested to play important roles in controlling an M. tb infection (Fol et al, 2015;Mao et al, 2015). In recent genome-wide association studies (GWAS) of TB risk in the Han Chinese population, new risk loci in ASAP1, ESRRB, and TGM6 genes have been identified (Chen et al, 2016a;Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…GWAS may provide insights into the genetic factors driving population susceptibility to viral infections [67,68]. This information can be utilized to identify populations within geographic regions at higher or lower risk of being infected with a new pathogen.…”
Section: Host-based Diagnostics and Genomics Approachesmentioning
confidence: 99%